Analisis Semantik Kata Nafaqah Dalam Surah An-Nisa Ayat 34 dan Relevansi Terhadap Putusan Nafkah Pengadilan Agama Indonesia - Pipin Novrianti (Journal of Social, Educational and Religious Studies, 2025)
Maintenance is a fundamental obligation in Islamic family law, serving to maintain the continuity and well-being of the household. The concept of maintenance has a strong normative basis in the Qur'an, particularly Surah An-Nisa', verse 34, which links the obligation to provide maintenance to the husband's leadership responsibilities (qiwāmah). This study aims to analyze the semantic meaning of the word "nafaqah" in Surah An-Nisa', verse 34, and examine its relevance to the determination of maintenance in Religious Court decisions in Indonesia. This study used a qualitative method with a library research approach and was descriptive-analytical in nature. Data were obtained from the Qur'an, classical and contemporary commentaries, Arabic semantic studies, laws and regulations, journals, scientific articles, and Religious Court decisions related to maintenance. The results indicate that semantically, nafaqah means the expenditure of assets that is obligatory, ongoing, and aimed at meeting the living needs of dependents. This meaning is not only linguistic, but also normative and social. The relevance of the semantic meaning of nafaqah is reflected in Indonesian positive law through the Marriage Law and the Compilation of Islamic Law, and is concretely implemented in the deliberations and rulings of Religious Courts, both in determining maintenance for wives and children, and post-divorce maintenance. Thus, the concept of nafaqah in Surah An-Nisa', verse 34, serves not only as a theological basis but also as an operational foundation in the Islamic family law system in Indonesia.